2011
DOI: 10.1002/pi.3103
|View full text |Cite
|
Sign up to set email alerts
|

Star poly(2‐ethyl‐2‐oxazoline)s—synthesis and thermosensitivity

Abstract: A series of star-shaped poly(2-ethyl-2-oxazoline)s was prepared by cationic polymerization. The polymerization was initiated by dipentaerythrityl hexakis(4-nitrobenzene sulfonate) and a tosylated hyperbranched polymer of glycidol. The polymerization proceeded in a controlled manner. The star structure of the products was determined by nuclear magnetic resonance. The molar mass distributions that were measured by gel permeation chromatography with multiangle laser light scattering were narrow, and the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 42 publications
4
70
1
5
Order By: Relevance
“…[15], [87] while higher plurifunctional initiators give tri-, tetra- etc. arm star polymers, [88] , bow-tie multi-arm stars [35] and ultimately, macroinitiators result in comb copolymers or at high grafting densities in molecular brushes (Figure 5). [89], [90] …”
Section: Introductionmentioning
confidence: 99%
“…[15], [87] while higher plurifunctional initiators give tri-, tetra- etc. arm star polymers, [88] , bow-tie multi-arm stars [35] and ultimately, macroinitiators result in comb copolymers or at high grafting densities in molecular brushes (Figure 5). [89], [90] …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, based on three independent reports on using sulfonate esters of pentaerythritol for the preparation of star-shaped poly(2-oxazolines) [16][17][18] it may be suggested that nosylates and triflates are better initiators than tosylates.…”
Section: Introductionmentioning
confidence: 99%
“…In the group of tetra-or hexavalent initiators, the best results were achieved using the porphyrin-cored tetra-tosylate initiator, whereas tetra-and hexa-tosylates lead to slow initiation and ill-defined polymers. Dworak and co-workers used dipentaerythrityl hexakis (4-nitrobenzenesulfonate) and tosylated hyperbranched polymers of glycidol (the latter with 13 initiating groups) as initiators for the CROP of EtOx [119]. The monomer consumption in the range 0-70% followed first-order kinetics [initiator: dipentaerythrityl hexakis (4-nitrobenzenesulfonate)].…”
Section: Multifunctional Tosylate and Triflate Initiatorsmentioning
confidence: 99%